2014
DOI: 10.1186/1471-2474-15-348
|View full text |Cite
|
Sign up to set email alerts
|

Visually assessed severity of lumbar spinal canal stenosis is paradoxically associated with leg pain and objective walking ability

Abstract: BackgroundLumbar spinal stenosis (LSS) is the common term used to describe patients with symptoms related to the anatomical reduction of the lumbar spinal canal size. However, some subjects may have a markedly narrowed canal without any symptoms. This raises the question of what is the actual role of central canal stenosis in symptomatic patients. The purpose of this study was to compare radiological evaluations of LSS, both visually and quantitatively, with the clinical findings of patients with LSS.MethodsEi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 33 publications
4
29
0
Order By: Relevance
“…Since this is the first study to evaluate this correlation, no references are available to state these results. Similar studies have been performed for other spinal diseases such as sciatica [12] or lumbar spinal stenosis [11,1921], displaying no correlation between imaging and clinical features, being in line with the current study. The suggestion that factors other than the spinal canal size alone, such as local neurovascular problems, venous obstruction or effect of local inflammatory cytokines–factors that are not identifiable at conventional MRI–contribute to differences in clinical manifestation of CES, seems sensible [18].…”
Section: Discussionsupporting
confidence: 92%
“…Since this is the first study to evaluate this correlation, no references are available to state these results. Similar studies have been performed for other spinal diseases such as sciatica [12] or lumbar spinal stenosis [11,1921], displaying no correlation between imaging and clinical features, being in line with the current study. The suggestion that factors other than the spinal canal size alone, such as local neurovascular problems, venous obstruction or effect of local inflammatory cytokines–factors that are not identifiable at conventional MRI–contribute to differences in clinical manifestation of CES, seems sensible [18].…”
Section: Discussionsupporting
confidence: 92%
“…It has already been shown in the literature that the ODI did not have a significant relationship with the area of the cross-section of the dural sac, or with the narrowing observed in radiological studies either in patients with and without spondylolisthesis. 12,26,27 The relationship was inversely proportional in the SSF-36. 17 However, there was no statistically significant correlation in this study, taking the PCS and MCS into account.…”
Section: Discussionmentioning
confidence: 93%
“…Chronic and neuropathic pain are particularly associated with cognitive impairment [7,8]. A past report showed that severe pain led to cognitive impairment in a longitudinal study [3]. We showed that neuropathic pain and numbness due to LDD were associated with cognitive dysfunction.…”
Section: The Relationship Between Ldd and Cognitive Functionmentioning
confidence: 56%
“…Lumbar degenerative disease (LDD), such as lumbar spinal stenosis (LSS), degenerative spondylolisthesis and spondylosis deformity, is more prevalent among middle-aged and elderly individuals. LDD causes low back pain, intermitted claudication, bladder and rectal disturbance, numbness and lower limb pain, and deterioration in muscle power of the lower limbs as well as standing and walking abilities [1][2][3]. The number of people whose quality of life (QOL) is impaired by LDD is expected to increase in a super-aging society.…”
Section: Introductionmentioning
confidence: 99%